Belajar dari Tradisi Para Sayid-Wali Songo di Nusantara: Learning from the Sayyids-Wali Songo’s Traditions in Nusantara - Ahmad Baso (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
Indonesian Islam has its own characteristics, being under the influence ofulama and kiai. The influence of these ulama on society has a big impact. Thespread of Islam in Indonesia in the 15th century was brought by Wali Songo.This research uses document research and direct reading methods fromprimary sources. In the spirit of preaching like this, the Wali Songo whospread Islam in this country are well aware that there is no use of spreadingIslam as a blessing if it turns out that the Indonesian people are experiencingdifficulties, are not harmonious, are destitute, are not living peacefully due tobeing at enmity with each other within the tribe. -ethnicity and race, so that itis not solid as a nation. In other words, Wali Songo's tolerance has its originsin the essence of the archipelago as Daru-s-Salam, especially in the substanceof the meaning of